Pet Therapy in Correctional Institutions: A Perspective From Relational-Cultural Theory. Issue 2 (3rd March 2016) - Thomas, Rita; Matusitz, Jonathan
Abstract : In this article the authors apply Relational-Cultural Theory to pet therapy in correctional institutions. An important premise is that when pet therapy is used in prisons a symbiotic relationship develops between pets and prison inmates which, at the same time, improve their relationships with people themselves. Relational-Cultural Theory posits that relationships with individuals are not just a means to an end. Rather, good relationships promote growth and healthy development; they also cultivate reciprocal empathy. Hence, a major reason of suffering for most people is their experience of isolation; healing can occur in growth-fostering relationships.